Live Borrelia burgdorferi preferentially activate interleukin-1 beta gene expression and protein synthesis over the interleukin-1 receptor antagonist. - Miller, L C (1992)
Lyme arthritis is one of the few forms of chronic arthritis in which the cause is known with certainty. Because cytokines are thought to contribute to the pathogenesis of chronic arthritis, we investigated the effect of the Lyme disease spirochete, Borrelia burgdorferi, on the gene expression and synthesis of IL-1 beta and the IL-1 receptor antagonist (IL-1ra) in human peripheral blood mononuclear cells. Live B. burgdorferi induced fivefold more IL-1 beta than IL-1 alpha and sevenfold more IL-1 beta than IL-1ra; LPS or sonicated B. burgdorferi induced similar amounts of all three cytokines. This preferential induction of IL-1 beta was most dramatic in response to a low passage, virulent preparation of B. burgdorferi vs. three high passage avirulent strains. No difference in induction of IL-1ra was seen between these strains. The marked induction of IL-1 beta was partially diminished by heat-treatment and abrogated by sonication; IL-1ra was not affected. This suggested that a membrane component(s) accounted for the preferential induction of IL-1 beta. However, recombinant outer surface protein beta induced little IL-1 beta. By 4 h after stimulation, B. burgdorferi induced sixfold more IL-1 beta protein than LPS. In contrast to LPS-induced IL-1 beta mRNA which reached maximal accumulation after 3 h, B. burgdorferi-induced IL-1 beta mRNA showed biphasic elevations at 3 and 18 h. B. burgdorferi-induced IL-1ra mRNA peaked at 12 h, whereas LPS-induced IL-1ra mRNA peaked at 9 h. IL-1 beta synthesis increased in response to increasing numbers of spirochetes, whereas IL-1ra synthesis did not. The preferential induction by B. burgdorferi of IL-1 beta over IL-1ra is an example of excess agonist over antagonist synthesis induced by a microbial pathogen, and may contribute to the destructive lesion of Lyme arthritis.